Symbol Analysis in the Poetry of Afif Bahktari - Rahyab , Mohammad Ibrahim (Integrated Journal for Research in Arts and Humanities, 2024)
Symbolism has evolved over centuries to express ambiguous concepts and has manifested in various forms in the thoughts and dreams of different writers. Symbolism encompasses thought and guides humanity into the realm of speechless contemplation. This article aims to meticulously study and extract various types of symbols in the poems of Afif Bahktari. By examining and analyzing this significant literary device in Bahktari's discourse, we will present the types of these symbols and their outcomes scientifically. Symbolic or symbolic poetry is a crucial current in contemporary poetry. According to many critics and theorists, contemporary poets are inclined towards symbolic poetry. Besides this viewpoint, other factors such as poets' familiarity with Western poetic movements and the symbolist school, changes in poets' perspectives towards existential and societal aspects, creation of artistic ambiguity, and deepening of poetry, can be mentioned. In fact, one of the objectives of employing symbols or symbols in the poetry of contemporary poets, including Afif Bahktari, is to create a vague and profound poetic fabric, influencing the audience and engaging them in the creation of poetic meaning, shifting poetry from a single-meaning state to a multi-meaning one, and prompting readers and audiences to pause and contemplate the meaning and concept of poetry. Therefore, this article attempts to address the important role of symbolism in Bahktari's poetry by interpreting and analyzing several symbols in his poems.